Optimasi Keandalan Proteksi melalui Pengujian Fungsi dan Karakteristik Overcurrent Relay dan Ground Fault Relay - Ruth Stevani Br Padang; Siti Anisah (CV. Hawari, 2026)
The reliability of an electrical protection system plays a highly crucial role in maintaining the continuity and stability of power distribution to consumers. One of the main factors determining this reliability is the performance of protection devices, particularly the Overcurrent Relay (OCR) and Ground Fault Relay (GFR). These relays act as the first line of defense in detecting and interrupting fault currents that occur within the electrical power system. Any inaccuracy in function, improper settings, or deviations in relay operating characteristics can lead to serious consequences, such as delays in fault clearing, expansion of the affected area, or even a complete failure of the protection system. This study aims to optimize the reliability of the protection system through functional and characteristic testing of the OCR and GFR installed at the Muara Teweh Substation, which operates under the jurisdiction of UP2D South and Central Kalimantan. The research methodology includes a series of tests on key parameters such as operating time, pickup current, time coordination between relays, and selectivity level in response to short-circuit and ground fault disturbances. The test data were analyzed to evaluate the conformity between actual performance and the predetermined relay settings. The results indicate that the relays at the Muara Teweh Substation are in good working condition and perform according to their expected characteristics. Recommendations for relay setting adjustments were also proposed to further improve protection system effectiveness. Through regular testing and proper calibration, the reliability of the protection system can be consistently maintained.